Visual folklore: relation between oral and visual memory - Stojanovik', Lidija (Wydawnictwo Naukowe UAM, 2012)
The aim of this article is to present how oral biography and photo-interviews are intertwined. In this sense, it is very important to illustrate the various methods of photo fieldwork, and also to highlight theoretical concepts (such as those of Panofsky, Collier and Barthes) in order to discover photo-analysis, the relation between oral and visual memory, and the phenomenological play between stadium and punctum. These principles are very important and useful in contemporary folklore studies.
Keywords: Photography; Visual folklore; Narrative; Studium; Punctum; Participant; Photoobservation; Fotointerview